2008
DOI: 10.2478/v10014-008-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

Response of tomato cultivars differing in growth habit to nitrogen and phosphorus fertilizers and spacing on vertisol in Ethiopia

Abstract: cropping seasons to investigate the response of tomato cultivars varying in growth habit to rates of Nitrogen (N) and Phosphorus (P) fertilizers and plant spacing. The treatment consisted of factorial combination of two cultivars (Margelobe and Melka shola), three NP fertilizers rates (50 kg N + 60 kg P 2 O 5 /ha, 80 kg N + 90 kg P 2 O 5 /ha and 110 kg N + 120 kg P 2 O 5 /ha) and three spacing (100 cm x 30 cm, 80 cm x 30 cm and 60 cm x 45 cm) arranged in a Randomized Complete Block Design. Results revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
27
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 3 publications
9
27
2
1
Order By: Relevance
“…Application of higher NP fertilizers rates gave greater average tomato fruit weight reported by Sharma et al [9].Highest row spacing results maximum fruit weight instead of closed row spacing in tomato reported by Ali [34]. Balemi [35] stated that higher nitrogen application gave greater fruit weight per plant in tomato. In contrast row spacing had no effect on fruit weight of tomato were reported by Jia and Rashid [36, 37] stated that fertilizer rates had no effect on average fruit of tomato.…”
Section: Number Of Fruits Kg -1mentioning
confidence: 85%
See 1 more Smart Citation
“…Application of higher NP fertilizers rates gave greater average tomato fruit weight reported by Sharma et al [9].Highest row spacing results maximum fruit weight instead of closed row spacing in tomato reported by Ali [34]. Balemi [35] stated that higher nitrogen application gave greater fruit weight per plant in tomato. In contrast row spacing had no effect on fruit weight of tomato were reported by Jia and Rashid [36, 37] stated that fertilizer rates had no effect on average fruit of tomato.…”
Section: Number Of Fruits Kg -1mentioning
confidence: 85%
“…Fruit weight per picking plot -1 was highly influenced by nitrogen levels and row spacing. Balemi [35]reported that, the highest number of fruits picking -1 plot -1 was influenced by high nitrogen and phosphorus rate.…”
Section: Number Of Fruits Kg -1mentioning
confidence: 99%
“…Farmers get lower yield mainly due to diseases, pests and sub-optimal fertilization [14]. Small-scale farmers, commercial growers and state farm enterprises grow the crop for its fruits in difference regions.…”
Section: Tomato Productionmentioning
confidence: 99%
“…Manipulation of plant spacing is an important means to increase light interception and its efficient use in tomato production (Feng et al, 2010). Tomato yield has been reported to be dependent on the number of plants accommodated per unit area (Mehla et al, 2000;Belemi, 2008;Maboko et al, 2011a). Castodi et al (2012) reported that an increase in plant density resulted in a reduction in mean fresh weight of the plants and increased productivity to a certain extent.…”
Section: Scientific Communicationmentioning
confidence: 99%
“…Castodi et al (2012) reported that an increase in plant density resulted in a reduction in mean fresh weight of the plants and increased productivity to a certain extent. Yield of fresh market and processing tomatoes was reported to be greatly influenced by plant spacing (Belemi, 2008). Mehla et al (2000) also reported the importance of plant spacing on yield and quality parameters in tomato crop.…”
Section: Scientific Communicationmentioning
confidence: 99%